Facile Synthesis of Novel Pyrano‐Pyrido‐Carbazole Scaffolds Using Magnetic Fe3O4 Nanoparticles as a Heterogeneous Green and Reusable Catalyst. Issue 37 (5th October 2020) - Parmar, Sarita; Sharma, Vikash; Jain, Shubha; Verma, Divya
Abstract: We reported a novel series of pyrano‐pyrido‐carbazol derivatives (PPCDs) 6(a‐o), synthesized via the reaction of 4‐hydroxypyridocarbazolone (3), aryl/heteroaryl aldehyde (4), and malononitrile (5), in water using Fe3 O4 magnetite nanoparticles (Fe3 O4 MNPs) as a heterogeneous novel catalyst at room temperature just in 60 mins under ultrasound. For this propose, Fe3 O4 MNPs with particle size 23.4±0.9 nm was successfully synthesized via a one‐step novel coprecipitation method in aqueous medium by the use of a new alkaline agent i. e . 2 ‐(ethylamino) ethanol and systematically characterized using field emission scanning electron microscopy (FESEM), high‐resolution transmission electron microscopy (HRTEM), energy dispersive analysis of X‐ray (EDAX), X‐ray diffraction (XRD), x‐ray photoelectron spectroscopy (XPS) and Fourier transformed infrared (FTIR). Fe3 O4 MNPs show remarkably dramatic dispersion stability as evident from zetapotential (ζ) value of −38.9 mV and hydrodynamic diameter (HD) of 238 nm and excellent specific surface area of 185 m 2 /g. Additionally, Fe3 O4 MNPs was easily separated after completion of the reaction, from the reaction mixture using the external magnet, and can be reused seven times without any considerable loss of its activity. The use of ultrasound made homogeneous dispersion of MNPs in water which accelerated the rate of reaction for the synthesis of PPCDs. This protocol has notable advantages like the synthesis of novel PPCDs with high yield in short reaction time, inexpensive catalyst, eco‐safe, and also favour green chemistry protocol. Abstract : A Fe3 O4 MNPs catalyzed multicomponent cascade reaction was developed for the facile synthesis of pyrano‐pyrido‐carbazol derivatives. Notable features of the protocol include a novel method for the synthesis of Fe3 O4 MNPs by the use of a new alkaline agent i. e . 2 ‐(ethylamino) ethanol, aqua‐mediated synthesis of novel PPCDs under ultrasound at room temperature with high yield in short reaction time, and also favour green chemistry protocol.